The emerging role of microRNAs in Alzheimer's disease - Femminella, Grazia D.; Ferrara, Nicola; Rengo, Giuseppe (Frontiers in Physiology, 2015)
MicroRNAs (miRNAs) are small non-coding RNA which have been shown to regulate gene expression. The alteration of miRNAs expression has been associated with several pathological processes, including neurodegeneration. In the search for easily accessible and non-invasive biomarkers for Alzheimer’s disease (AD) diagnosis and prognosis, circulating miRNAs are among the most promising candidates. Some of them have been consistently identified as AD-specific miRNAs and their targets also seem implicated in pathophysiological processes underlying AD. Here, we review the emerging role for miRNA in AD, giving an overview on general miRNAs biology, their implications in AD pathophysiology and their potential role as future biomarkers.